Herding Behavior in the Indonesia Stock Exchange - Abundanti, Nyoman; Candraningrat, Ica Rika; Mustanda, I Ketut (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to detect and analyze the indications of herding behavior on the stock exchange in Indonesia. Herding detection method uses Cross Sectional Absolute Deviation. The data needed is the daily return of actively traded individual stocks and the daily return of the Composite Stock Price Index on the Indonesia Stock Exchange in 2015-2018 The analytical method used to test the hypothesis is multiple regression analysis. Based on the results of the analysis conducted, it was concluded that the results showed that there was a significant and positive relationship between individual stock returns and market returns with the dispersion value (CSAD), as an indication of the absence of herding behavior on the Indonesian stock exchange. This condition can mean market participants can use strategy and be oriented as an investor, both investor growth and value investors. Because there is no indication of herding behavior, the Indonesian stock exchange has an efficient condition, so that market participants can utilize the available information as a reference in conducting transaction strategies.